Measurability and feasibility of work in the management of an industrial enterprise in a flexible production environment. Issue 10 (2022) - Smirnova, G.; Sabitov, R.; Elizarova, N.; Sabitov, Sh.; Eponeshnikov, A.; Maximova, N.
Abstract: The issues of measurability and evaluation of work and various services, the feasibility of orders in production systems have been studied by many authors. Here we consider the development of these methods for organizing the management of manufacturing enterprises in the context of the transition to flexible production. The necessary and sufficient conditions for the feasibility of the work are formulated. Examples of providing car rental at specified time intervals and evaluating the feasibility of requests for equipment repair in a service center in the structure of a machine-building enterprise are considered.